Breeding Phenology and Meteorological Conditions Affect Carer Provisioning Rates and Group-Level Coordination in Cooperative Chestnut-Crowned Babblers - Nomano, Fumiaki Y.; Savage, James L.; Browning, Lucy E.; Griffith, Simon C.; Russell, Andrew F. (Frontiers in Ecology and Evolution, 2019)
Recent theoretical and empirical work suggests that coordinating offspring provisioning plays a significant role in stabilising cooperative care systems, with benefits to developing young. However, a warming and increasingly extreme climate might be expected to make contributions to, and so coordination of, care more challenging, particularly in cooperative breeding systems comprising multiple carers of varying age and pair-wise relatedness. Here we investigated the interplay between breeding phenology, meteorological conditions and carer number on the individual rates and group-level of coordination of nestling care in the cooperatively breeding chestnut-crowned babbler (Pomatostomus ruficeps) in outback south-eastern Australia. From three months since the last meaningful rain event, dominant male breeders and – to a lesser extent – related helpers showed reductions in their provisioning rates and increases in their day-to-day variation. On days with high mean wind speed, dominant males contributed less and helpers were less likely to visit the nest on such days, and also showed reduced visitation rates on days with high mean temperature. Provisioning rates were independent of the number of carers, and increasing numbers of carers failed to mitigate the detrimental effects of challenging environment on patterns of provisioning. Those helpers that were unrelated to broods often failed to help on a given day and tended to help at a low rate when they did contribute, with socio-environmental predictors having limited explanatory power. Given the marked variation in individual contributions to offspring care and the variable explanatory power of the socio-environmental predictors tested, babblers unsurprisingly had low levels of nest-visitation synchrony. Large groups visited the nest more asynchronously on days of high mean temperature, suggesting that meteorological impacts on individual provisioning have consequences for group-level coordination. Our study has implications for the consequences of climate change on patterns of provisioning, the minimal role of group size in buffering against these challenges and the stabilisation of cooperative care.